Pengaruh Aktivitas Akuatik terhadap Kualitas Tidur Anak Autism Spectrum Disorder (ASD) Usia 3 sampai 9 Tahun di Klinik Hafidz Center Mojolaban Sukoharjo - Kurniawati, Linda; Saloko, Erayanti (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background:  Autism is a complex developmental disorder that affects communication and behavior as a result of sensory problems. Sensory disorders are one of the causes of ASD children experiencing sleep quality problems. To reduce sleep problems in children with ASD is by providing aquatic activities. Objectives: Aquatic activities can provide sensory input and are calming, so they can improve the sleep quality of children with ASD. The aim of this study was to find out whether there is an influence of aquatic activities on the sleep quality of children with autism spectrum disorder (ASD). Methods: This research is a quantitative research with a Quasi Experimental Pretest-Posttest design with Non-Equivalent Control-Group Design. Sleep quality was measured using The Pittsburgh Sleep Quality Index (PSQI) with the help of the SPSS 24 statistical program. Results: The results of data analysis, it was found that the majority of samples were male, 84.6% in the intervention group and 76.9% in the control group, the highest age level of respondents was 5-6 years old, 38.5% in the intervention group and 53.8% in the control group, education the majority of parents in the intervention and control groups were high school seniors at 46.2%, the majority of Autism Quotient scores had an average value of 69.2% in the intervention group and 46.2% in the control group. The significance value in the control group was 0.673 (above 0.05), which means there was no difference in sleep quality scores in the first and second measurements. The significance value in the intervention group was 0.007 (below 0.05), which means there was a difference in sleep quality scores before and after the aquatic intervention. Conclusion: Aquatic activities influence the sleep quality of children with autism spectrum disorder (ASD) aged 3 to 9 years at the Hafidz Center Clinic Mojolaban Sukoharjo. Keywords: Autism, Sleep Quality, Aquatic Activity